N-Alkyl derivatives of diosgenyl 2-amino-2-deoxy-β-D-glucopyranoside; synthesis and antimicrobial activity - Walczewska, Agata; Grzywacz, Daria; Bednarczyk, Dorota; Dawgul, Małgorzata; Nowacki, Andrzej; Kamysz, Wojciech; Liberek, Beata; Myszka, Henryk (Beilstein Journal of Organic Chemistry, 2015)
Diosgenyl 2-amino-2-deoxy-β-D-glucopyranoside is a synthetic saponin exhibiting attractive pharmacological properties. Different pathways tested by us to obtain this glycoside are summarized here. Moreover, the synthesis of N-alkyl and N,N-dialkyl derivatives of the glucopyranoside is presented. Evaluation of antibacterial and antifungal activities of these derivatives indicates that they have no inhibitory activity against Gram-negative bacteria, whereas many of the tested N-alkyl saponins were found to inhibit the growth of Gram-positive bacteria and human pathogenic fungi.
Keywords: antimicrobial activities; D-glucosamine; diosgenin glycosylation; N-alkylation